Metode Pengendalian Wideng (Sesarma spp) Hama Bibit Mangrove melalui Kegiatan Budidaya Kepiting Bakau Scylla spp - Hidayat, Jafron Wasiq (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2011)
Reboisation is one strategy to anticipate global warming that most easily performed. This re-plantingactivity is very urgent to be conducted in mangrove areas, since the impact of global warming are very profound atthe coastal and lowland areas. Its implementation has been done, but failures are still high. One of the causes oftenfound in the field is pests. Its efficient and effective control are still faces various obstacles. Wideng (Sesarma) isvery often perform as pest to the mangrove propagules, therefore could affect the community structure. It is thereforeimportant to establish conceptual study and research on wideng control, especially those that are able to promoteparticipation and benefit the community. One potential control is to empower its natural predators, the mud crabScylla. The purpose of this research is to analyze the level of Scylla predation, namely of total prey consumed, preysize and prey density presentation. It is also intended to determine weight gain and predation behavior byScylla. Two units of the test cage were placed in the pond in Tapak Tugurejo Semarang with Complete RandomizedDesign (3 treatments and 5 replications). Data on predation tests are descriptively and statistically analyzed usingJMP software, whereas the study of behavior was analyzed descriptively.The results demonstrated that Scylla is able to prey and consume wideng namely the life ones. Scyllaperform no respecter of prey body size, since wideng of small body size (2-3 cm), preferably the same to themoderate size (4-5cm) and large size (> 5 cm). The level of consumption gives a high weight gain for Scylla,between 182 - 197% in just 6 days. In term of presentation of the treatment, showed that wideng really liked thepresentation of the feed lot at once rather than presenting a slightly but gradually. Finally, feeding on Scylla withwideng through cultivation, particularly in fattening purposes, using wideng is reasonable and flexible to be appliedfor fishermen. This concept, together with other control components (components of a dissertation study of theauthor), is very supportive on the wideng control whiles provide economic benefits to the society atonce.